Kardiochirurgia DorosłychChirurgiczna ablacja prądem o częstotliwości radiowej u pacjentów z utrwalonym migotaniem przedsionków. Wyniki krótko- i średnioterminowe wybranych parametrów echokardiograficznych i biochemicznych - Guzy, Michał; Krejca, Michał; Goliszek, Leszek; Durałek, Andrzej; Skarysz, Janusz; Bis, Jarosław; Bochenek, Andrzej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Background: Atrial fibrillation (AF) often accompanies coronary heart disease, arterial hypertension and mitral valve failure. The absence of atrial systolic function and irregular ventricular rhythm influences left ventricle ejection fraction (EF). It is estimated that AF reduces EF by nearly 20%. Moreover, AF is associated with elevated serum levels of natriuretic factors, such as atrial natriuretic peptide (ANP). It is reported that restoration of sinus rhythm (SR) leads to significant improvement of left ventricle EF and normalizes ANP levels. Aim: was to evaluate changes in echocardiographic parameters and serum levels of ANP after surgical radiofrequency ablation of AF. Material and methods: The study group comprised 64 patients (mean age 65.6±6.9) with mitral valve failure and permanent atrial fibrillation lasting more than 6 months. As an additional procedure to mitral valve surgery radiofrequency ablation (RFA) in the left atrium was performed. During follow-up visits ECG and echocardiography were used to assess the effectiveness of RFA. Serum levels of ANP were measured before and on the first and second day after the procedure. Results: Early after the operation sinus rhythm was restored in 40 (62.5%) patients (SR group). The rest of the patients still suffered from AF during the in-hospital period (non-SR group). Preoperatively the serum levels of ANP were within normal limits in both groups. Postoperatively mean ANP concentration decreased in the SR group but did not in the non-SR group. Moreover, on the second day the mean level in the non-SR group was markedly higher. One year after the operation the number of patients with SR increased to 45 (70.3%). Control echocardiography showed a significant increase in EF within one year of follow-up. Moreover, left atrium diameter and its area decreased during the observation period. Conclusions: The maintenance of SR within 1 year of follow-up leads to a significant increase of left ventricle EF and decrease of left atrium size. Restoration of sinus rhythm leads to a significant decrease in ANP concentration in the early postoperative period. The lack of sinus rhythm postoperatively may be associated with increased levels of ANP.